2007
DOI: 10.1016/j.vetpar.2007.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Field study on nematode resistance in Nelore-breed cattle

Abstract: The present study evaluated Nelore cattle with different degrees of resistance to natural infections by gastrointestinal nematodes. One hundred weaned male cattle, 11-12 months of age, were kept on the same pasture and evaluated from October 2003 to February 2004. Faecal and blood samples were collected for parasitological, haematological and immunological tests. In February 2004, the 10 most resistant and the 10 most susceptible animals were selected based on individual means of nematode faecal egg counts (FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…These results suggested that F200Y (T A C) resistance mutation is likely to be present in many H. placei populations of buffalo and cattle. Previously benzimidazole resistance has been reported in H. placei in Brazil (Bricarello et al, 2007), Argentina (Anziani et al, 2004), USA (Gasbarre et al, 2009b; Gasbarre et al, 2009a) and north India (Yadav and Verma, 1997), but there is little information on its prevalence. These reports are based on faecal egg count reduction tests (FECRTs) to give an estimate of the benzimidazole resistance or susceptibility status of a parasite community as a whole, but cannot be used to assess the proportion of benzimidazole resistance worms in a particular population (Achi et al, 2003; Jacquiet et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that F200Y (T A C) resistance mutation is likely to be present in many H. placei populations of buffalo and cattle. Previously benzimidazole resistance has been reported in H. placei in Brazil (Bricarello et al, 2007), Argentina (Anziani et al, 2004), USA (Gasbarre et al, 2009b; Gasbarre et al, 2009a) and north India (Yadav and Verma, 1997), but there is little information on its prevalence. These reports are based on faecal egg count reduction tests (FECRTs) to give an estimate of the benzimidazole resistance or susceptibility status of a parasite community as a whole, but cannot be used to assess the proportion of benzimidazole resistance worms in a particular population (Achi et al, 2003; Jacquiet et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The immunological and clinical pathological parameters in both cohorts were then compared. The approach taken in this study, to compare the immunological responses in animal with a large disparity in burden is not unique and has been used previously as a first effort to address natural resistance in other parasite classes (34)(35)(36)(37). The variability observed here could have arisen from sources other than host resistance, in particular experimental variation.…”
Section: Discussionmentioning
confidence: 99%
“…1), when the averages for the two genetic groups were very near each other. Various studies conducted in Brazil have shown there are no associations between the levels of infection by nematodes and PCV values (Nicolau et al, 2002;Bricarello et al, 2007;Oliveira et al, 2009). Although it was not possible to detect alterations in the PVCs of the animals, it is known that gastrointestinal nematode infections can have a negative impact on food intake, causing significant declines in herd productivity (Frisch, 1999;Frisch et al, 2000;Stromberg and Gasbarre, 2006).…”
Section: Discussionmentioning
confidence: 99%